Preliminary research on production and interference characteristic of one multiband smoke material - Weidong, X.; Heng, L.; Jianhua, W.; Jinsong, Z. (Materials research innovations, 2015)
Laser, thermal infrared and television guidance weapons play critical roles in actual combat fields. This article aims to research and develop a smoke-generating material, which is able to shield visible lights, thermal infrared and millimetre wave with the attenuation characteristic of expandable graphite to thermal infrared and millimetre wave, and to test and verify the multiband interference effect of combustion products. Test results reveal the desired interfering capacity of the target material.